Biomechanical Evaluation of Seven Fixation Methods for Sagittal Split Ramus Osteotomy with Four Advancement Levels by Finite Element Analysis - He, Yu; Zhang, Henglei; Qiao, Jia; Fu, Xi; Xu, Shixing; Jin, Qi; Liu, Jianfeng; Chen, Ying; Yu, Bing; Niu, Feng (Frontiers in Surgery, 2022)
Background Mandibular sagittal split ramus osteotomy (SSRO) is a routine surgery to correct mandibular deformities, such as mandibular retrusion, protrusion, deficiency, and asymmetry. However, nonunion/malunion of the fragments and relapse caused by fixation failure after SSRO are major concerns. Rigid fixation to maintain postosteotomy segmental stabilization is critical for success. Additionally, understanding the biomechanical characteristics of different fixation methods in SSRO with large advancements is extremely important for clinical guidance. Therefore, the aim of the present study was to evaluate the biomechanical characteristics of different SSRO methods by finite element analysis. Methods SSRO finite element models with 5-, 10-, 15-, and 20-mm advancements were developed. Seven fixation methods, namely, two types of bicortical screws, single miniplate, dual miniplates, grid plate, dual L-shaped plates, and hybrid fixation, were positioned into the SSRO models. Molar and incisal biomechanical loads were applied to all models to simulate bite forces. We then investigated the immediate postoperative stability from four aspects, namely, the stability of the distal osteotomy segment, osteotomy regional stability, stress distribution on the mandible, and implant stress performance. Results The stability of the distal osteotomy segment and osteotomy region decreased when the advancement increased. All seven fixation methods displayed favorable biomechanical stability under minor advancement (5 mm). With large advancements, bicortical screws, dual miniplates, and grid plates provided better stability. The von Mises stress was concentrated around the screws close to the osteotomy region for the proximal segment for all fixation methods, and the von Mises stress on implants increased with larger advancements. With small advancements, five fixation methods endured tolerable maximum stresses of <880 MPa. A single miniplate and dual L-shaped plates generally suffered high stresses using larger advancements. The biomechanical characteristics were similar under molar and incisal loads. Conclusions The current study investigated the biomechanical properties of seven fixation devices after SSRO under molar and incisal loads. Generally, bicortical screws, grid plates, and dual miniplates provided better biomechanical stability using finite element analysis.